2016
DOI: 10.3389/fpsyg.2016.01134
|View full text |Cite
|
Sign up to set email alerts
|

Adaptability and Life Satisfaction: The Moderating Role of Social Support

Abstract: The purpose of this study was to investigate the moderating role of social support in the relationship between adaptability and life satisfaction. Data were collected from 99 undergraduate freshmen in a Chinese university using a lagged design with a 1-month interval. Results demonstrated that social support moderated the relation between adaptability and life satisfaction, such that the positive relation between adaptability and life satisfaction was stronger for individuals with higher levels of social suppo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
104
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(116 citation statements)
references
References 49 publications
(61 reference statements)
11
104
0
1
Order By: Relevance
“…Recent research about student's transition to college established the positive relation between adaptability and life satisfaction [8]. The accomplishment of this transition depends on student's wellbeing, and how they face and surpass their challenges [6,9].…”
Section: Academic Life Satisfactionmentioning
confidence: 99%
“…Recent research about student's transition to college established the positive relation between adaptability and life satisfaction [8]. The accomplishment of this transition depends on student's wellbeing, and how they face and surpass their challenges [6,9].…”
Section: Academic Life Satisfactionmentioning
confidence: 99%
“…Social support in the process of coping with SCI is significant (10). Several studies show that more social support is related to PTG (11)(12)(13) and life satisfaction (14,15). Social support is defined as the process of interaction in relationships, which improves coping, esteem, respect, love, belonging through actual or perceived exchanges of physical or psychosocial resources, which can reduce the pressure on people (15).…”
Section: Introductionmentioning
confidence: 99%
“…Of relevance to the present study, there is wealth of research emphasizing the importance of social support during adolescence and emerging adulthood (e.g., Arnett, 2000;DuBois et al, 2002;Pettit et al 2011;Zhou & Lin, 2016). For example, Zhou and Lin (2016) recently found that social support played a moderating role in the relationship between adaptability and life support among adolescents. More specifically, researchers illustrated that social support was able to strengthen the nature of the observed relationships and positive outcomes.…”
Section: Social Environmentmentioning
confidence: 85%
“…Beyond serving as a buffer against the adverse effects of negative experiences, there is also evidence suggesting that social support may enhance the benefits of factors that are associated with positive outcomes (Cohen & Wills, 1985). For example, Zhou and Lin (2016) recently demonstrated that social support moderated the association between adaptability and life satisfaction, despite the absence of a stressor. In a sample of first year university students transitioning from high school to post-secondary studies, it was found that higher levels of perceived social support strengthened the positive relationship between adaptability and life satisfaction, in comparison to students who experienced lower levels of social support (Zhou & Lin, 2016).…”
Section: Social Environmentmentioning
confidence: 99%
See 1 more Smart Citation